Confirmed cases and mortality from COVID-19 in South America: a comparative analysis per million inhabitants - Berrocal Huamani, Nelson (2020)
This article shows a comparison of confirmed cases and death from Coronavirus disease (COVID-19), among South American countries, considering cases per million inhabitants and standardizing the time of infection, from the day of confirmation of case zero to each country. The objective is to more uniformly evaluate the spread of this virus and thus evaluate the result of the measures taken by governments against COVID-19, since various research centers show comparisons without taking into account the proportion of inhabitants, nor the time (days) of contagion between countries. In addition, we provide short-term predictions and an estimate of the end of confirmed cases in the most affected countries.